2019
DOI: 10.1589/jpts.31.277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heart failure on functional recovery after hip fracture

Abstract: [Purpose] Heart failure has been identified as a risk factor for reduced physical function and falls; however, the impact of heart failure on functional recovery after a hip fracture is unclear. This study aimed to examine how heart failure and pre-fracture physical function affect recovery after a hip fracture. [Participants and Methods] The study population consisted of 122 patients with sub-acute hip fracture (mean age 81.7 ± 9.7 years, 18.9% male) who were divided into two groups: heart failure and non-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
3
1
Order By: Relevance
“…We found that 21.9% of patients with hip fracture also had heart failure. In two earlier studies, the reported frequencies at which heart failure accompanied hip fractures were 13.9% and 13.3%, respectively [37,38]. The reason for higher frequency of complicating heart failure in the present study may be the different definition of heart failure.…”
Section: Discussioncontrasting
confidence: 49%
“…We found that 21.9% of patients with hip fracture also had heart failure. In two earlier studies, the reported frequencies at which heart failure accompanied hip fractures were 13.9% and 13.3%, respectively [37,38]. The reason for higher frequency of complicating heart failure in the present study may be the different definition of heart failure.…”
Section: Discussioncontrasting
confidence: 49%
“…Mathew et al [ 12 ] also reported that maximum functional improvement occurs during the first 6 months after rehabilitation in a self-reporting heart failure group, and that this group had a lower level of recovery of transfer ability and locomotion than a group without disease. Itagaki et al [ 13 ] recently reported that hip fracture patients with heart failure showed lower REs during hospitalization than those without heart failure, even after adjustment for confounding factors. These three studies appear to indicate that heart failure negatively affects the ADL improvement achieved through rehabilitation; however, the diagnosis of heart failure in the first two studies was based on self-reported histories, and the diagnosis of heart failure in the third study was retrospectively confirmed based on medical records.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Similarly, FIM effectiveness was reportedly reduced in hip fracture patients with a history of heart failure. [ 13 ] However, because these two studies relied on self-reported diagnoses of heart failure or retrospectively confirmed heart failure diagnosis based on the medical record, the degree and severity of heart failure during rehabilitation could not be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The MBDS does not include variables concerning New York Heart Association (NYHA) functional class, natriuretic peptide values, left ventricular ejection fraction, or drugs administered for heart failure during hospitalization. The purpose of our study, in contrast to others [ 40 , 41 ], was not to evaluate the functional situation of the patients but rather the association of the presence of heart failure with the in-hospital mortality and readmission.…”
Section: Discussionmentioning
confidence: 98%